Searching for the equity premium - Bai, Hang; Zhang, Lu (Journal of Financial Economics, 2022)
A dynamic stochastic general equilibrium model with recursive utility, search frictions, and capital accumulation is a good start to forming a unified theory of asset prices and business cycles. The model reproduces an equity premium of 4.27% per annum, a stock market volatility of 12.42%, and an average interest rate of 1.97%, while retaining plausible business cycle dynamics. The equity premium and stock market volatility are strongly countercyclical, whereas the interest rate and consumption growth are largely unpredictable. Because of wage inertia, dividends are procyclical despite consumption smoothing via investment. The welfare cost of business cycles is huge, 33.6%.